Dupilumab in patients with bullous pemphigoid and concomitant atopy - Jobst, Katerina; Künzel, Stephan R.; Beissert, Stefan; Abraham, Susanne (Frontiers in Pharmacology, 2025)
BackgroundBullous pemphigoid (BP) and atopic dermatitis (AD) are chronic inflammatory skin diseases that may share overlapping immunopathogenic mechanisms, particularly a type 2 immune response. Emerging evidence suggests that dupilumab, an IL-4Rα antagonist, may be effective in treating both conditions.MethodsIn this retrospective case series, twelve patients (mean age: 78.6 years; range: 67–93 years) with moderate to severe BP and a history of AD were included. All patients received dupilumab and were monitored over 12 weeks. Clinical activity was assessed using BPDAI scores, pruritus NRS, and DLQI.ResultsAt week 12, complete remission of bullous skin lesions was observed in all patients (100%), with 83.3% already achieving this by week 4. Pruritus improved significantly (p < 0.0001), with 58.3% achieving complete resolution (NRS 0/10) at week 12. Notably, two patients had previously received tralokinumab without clinical improvement, underscoring the distinct efficacy of dupilumab in this setting. Patient satisfaction was uniformly high (score 5/5). No adverse events were reported. Dupilumab was well tolerated, even in elderly, multimorbid patients.ConclusionDupilumab appears to be a safe and highly effective treatment for patients with concurrent BP and AD, leading to rapid and sustained symptom control, resolution of skin lesions, and high patient satisfaction.